Wetlands, livelihoods and human health - McCartney, Matthew P.; Rebelo, Lisa-Maria; Senaratna Sellamuttu, Sonali (2015)
In developing countries millions of people live a life of subsistence agriculture, mired in poverty, with limited access to basic human needs, such as food and water. Under such circumstances wetlands, through the provision of a range of direct and indirect ecosystem services, play a vital role in supporting and sustaining peoples’ livelihoods and hence, their health. This chapter discusses the role of wetlands in the context of the sustainable livelihoods framework in which wetlands are viewed as an asset for the rural poor in the form of “natural capital”. The framework is used to illustrate how ecosystem services, livelihoods and health are entwined and how the ecosystem services provided by wetlands can be converted to human health either directly or via other livelihood assets. It highlights the contributions that wetlands make to basic human needs and, either directly or through transformations to other forms of livelihood capital, the support they provide to livelihoods and overall well-being.